Gingival squamous cell carcinoma: A diagnostic impediment - Rekha Rani Koduganti; Sangeeta Sehrawat; P Veerendra Nath Reddy (Wolters Kluwer Medknow Publications, 2012)
Oral squamous cell carcinomas represent 3% of cancers in men and 2% of cancers in women. More than 90% of oral cancer occurs in people older than 45 years Lesions of gingiva account for approximately 10% of the oral squamous cell carcinomas and may present clinically as an area of ulceration, exophytic mass, or red/white speckled patches. The proximity to the underlying periosteum may invite early bone invasion. Carcinoma of gingiva constitutes an extremely important group of neoplasms as the lesion frequently mimics the reactive and inflammatory conditions affecting the periodontium, delaying the diagnosis and making the prognosis of the patient poorer. A rare case of gingival squamous cell carcinoma has been reported here, in a 40 Year old male patient. Careful recording of the case history and results of clinical examination, radiographic, and laboratory investigations, along with a critical review of similar conditions led to the diagnosis, and treatment was initiated.